DAYA TANGGAP KUALITAS PELAYANAN PERAWAT PASIEN RAWAT INAP BEDAH DI RSUD LABUANG BAJI - Irma Muslimin; Nurhayati Nurhayati (Politeknik Kesehatan Kemenkes Mamuju, 2016)
Development of health as one of the national development efforts for the achievement of awareness, willingness and ability to live a healthy life for every resident in order to realize optimal health status. This study aims to determine responsiveness to service quality inpatient surgical nurse at the Hospital Labuang Makassar Baji. The study population was the whole patient/client while undergoing inpatient surgery in hospitals Labuang Baji. with the number of 211 patients. Sampling patients were calculated using a minimum sample size with number of 86 patients. The results showed that the quality of nursing service inpatient surgery is reviewed capability of quickly handling patient complaints values ​​obtained Beta 0.414 (positive) aspects of fast action when a patient requires values ​​obtained Beta 0.310 (positive) and the aspect of providing information that is clear and easily understandable obtained Beta value of 0,303 (positive). Hospital Labuang Baji should hold regular training to nurses in order to improve the ability of nurses to handle patient complaints quickly.